2004
DOI: 10.1016/j.ejcts.2004.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of FK633, an ultra-short acting glycoprotein IIb/IIIa antagonist on platelet preservation during and after cardiopulmonary bypass

Abstract: An ultra-short acting glycoprotein IIb/IIIa antagonist, FK633, is effective in preventing both platelet aggregation and thrombocytopenia during CPB, and may be effective for minimizing postoperative bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This systematic review and meta-analysis showed that thrombocytopenia has a considerable prevalence (up to 21%) in ECMO patients. Thrombocytopenia has been demonstrated in patients undergoing different mechanical circulatory support (cardiopulmonary bypass, intra-aortic balloon pump, left ventricular assist device (LVAD)) [41][42][43][44][45][46] (Figure 4 in Supplemental material). The origin of thrombocytopenia is likely multifactorial (contact with foreign surfaces, platelet activation, inflammatory and coagulative cascade activation), with sepsis, medications, surgery, bleeding, intravascular devices, and blood transfusions as contributing factors [41][42][43] (Figure 3 and Figure 4 in Supplemental material).…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review and meta-analysis showed that thrombocytopenia has a considerable prevalence (up to 21%) in ECMO patients. Thrombocytopenia has been demonstrated in patients undergoing different mechanical circulatory support (cardiopulmonary bypass, intra-aortic balloon pump, left ventricular assist device (LVAD)) [41][42][43][44][45][46] (Figure 4 in Supplemental material). The origin of thrombocytopenia is likely multifactorial (contact with foreign surfaces, platelet activation, inflammatory and coagulative cascade activation), with sepsis, medications, surgery, bleeding, intravascular devices, and blood transfusions as contributing factors [41][42][43] (Figure 3 and Figure 4 in Supplemental material).…”
Section: Discussionmentioning
confidence: 99%
“…Typical pharmacologic means have focused on anti-fibrinolytic agents but could also focus on intraoperative adjuncts for the prevention of platelet dysfunction (7, 22) or the promotion of hemostasis with fibrinogen concentrate (21) or recombinant factor VII (23). The etiology of preoperative anemia in patients undergoing elective cardiac operations has been described and it is suggested that in the majority of patients the anemia is preventable (24).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide has the advantages of being very short-acting and may be administered via the oxygenator, which has the largest surface area for contact activation of the CPB circuit. The ultrashort-acting glycoprotein IIb-IIIa antagonist FK633 was shown to be effective in preventing CPB-induced thrombocytopenia and preventing platelet adhesion to the circuit (101). Little attention has been given to platelet anesthesia in pediatric cardiac surgery, but attenuation of the platelet response seems an obvious therapy to 'complete' anticoagulation for CPB.…”
Section: Platelet Anesthesiamentioning
confidence: 99%